MISTICISMO E PROTESTANTISMO: UM ESTUDO FENOMENOLÓGICO DAS EXPERIÊNCIAS RELIGIOSAS - Pazinato, Patrícia (2005)
The present thesis investigates the manifestations of mysticism in the Brazilian Protestantism, especially in its origins, having as observation field the activity missionary. This work is registered in the middle of studies that approach the relations between culture, religion and modernity, mainly when related with the symbolic field. It is a exploratory research based on phenomenons´study . For that , it is used phenomenons´ study reduction and the eidética reduction as the orientations of Edmund Husserl. This thesis attempts to bring contributions to clarify elements presents in the construction, transformation and diffusion of the Protestantism, considering the protestant mystic as a religious phenomenon. The mystic experience is analyzed in the individual and collective point of view, once this work privileges a sociological perspective in interface with Psychology, the Anthropology and, less centrally, the Philosophy and History. As qualitative research and delimited by its object of study, the mysticism can initially be pointed as a direct relation between sacred and the loyal , recognized in this manner individually and for the group that belongs. As theoretical reference, among others authors, the ideas of sociologist Roger Bastide were used, confirming or to refuting its hypothesis that argues that one of the meanings of the mysticism could represent the emergency of the sacred savage. This expression assigns the presence of symbolic elements that are manifested in spontaneous or explosive way in the religious rituals. Processes as the secularizing and the laicização, caused by the institutionalization and modernity of the religion, cause the manifestation of sacred savage, showing the residues of the occult or apparently exactly latent social-cultural productions. The instruments used for the accomplishment of the research are stretches of characteristic literary compositions of the Protestantismo as The Pilgrim and the Pilgrim of authorship of John Bunyan, as well as periodicals and Brazilian evangelical periodic to the second half of century XIX: The Standard, Puritan a nd Christian Expositor, that transmitted conceptions of the Puritanism and the Pietism. Daily autobiographicals text and stretches of the missionaries complement the analysis. The work is placed historically in the antecedent period to the one of the Reformation, its development and unfoldings. The movements of English and American revival had been prioritized especially. in its respective influences in the imaginary and Brazilians religious practical. After careful reading, election and organization for unit of the analyzed data, it was firmed hypothesis that argues that the protestant mystic is a constituent element of the Protestantism, representing modalities of social meaning, among which the cultural mediations are distinguished between: reason /emotion; singularization/institucionalizing; fragmentation/unity; tradiction/inovation; e padronization/autonomy, expressing relations with the forms of power, social change and divergence of social-economic interests. It was verified the existence, mainly in the less privileged social classes of the population, of important ind ication of cultural approach betwen some religious practical elements of the centecostalism together whit the African and aboriginal symbolic field. It is suggested that new research could be made, disclosing to the meanings of the mystics forms of expression in the Brazilian Protestantism and its relations with the Pentecostalism. These investigations can clarify the processes of juxtaposition of distinct cultural elements in the Brazilians religious practical, as affirmed by Roger Bastide, and corroborated for this research.